The importance of learning and acquiring grammatical concepts (Journal of the College of Basic Education, 2023)
Summary of the research:The subject of concepts received great attention from scientists, researchers, and educators, especially those interested in the subject of knowledge and building knowledge. Concepts to facilitate learning and education processes. It has become very difficult in the educational arena to put the learner in front of the large amount of information and the many types of knowledge that educational institutions have crowded with and the continuous increase in the world of information. The great change that affected a lot of knowledge and information had the greatest impact on the renewal of the movement Learning and education in the world, and from here began the subject of concepts to play a major and important role in the formation of knowledge and learning and acquisition of information (Atiyah, 2015, 76)